Pengembangan Model Pembelajaran Kepenyiaran Radio dengan Pemanfaatan Streaming Radio sebagai Upaya PembentukanLife SkillBagi Mahasiswa - Kusumaningsih, Dewi (Universitas Muhammadiyah Surakarta, 2016)
This study examines the importance of developing learning model of radio broadcasting as a means of facilitating cognitive competencies and life skill for the students. The purposes of this study are (1) to describe the development of radio broadcasting learning model, (2) to prove that radio broadcasting learning can teach life skill the students. The method used is research and development (R & D). The research is a preliminary study that includes (1) The field study on the learning model of radio broadcasting in PBSI Veteran Bangun Nusantara University lasted 2 years; (2) Stage description and analysis of findings; (3) Phase of drafting a learning model development and test radio broadcasting limited to science communication specialists. The data used are Â the Events Unit Class (SAP), the value of the fourth semester student at the college broadcasting PBSI, teaching faculty journals, and interviews. The results obtained are learning radio broadcasting fourth semester of academic year 2014/2015 was limited to conventional methods that rely lecture techniques and the use of textbooks. Students are invited to visit the study just outside the campus radio to simply look how the broadcaster broadcasts. Learning skills are not trained life skill which covers various techniques of designing a radio broadcast of the event, made a rundown of events, made hot clock radio broadcast, live events in studio practice until the practice of streaming radio.